Discontinuation of Corruption Investigation and Prosecution: A Comparison of Indonesia, The Netherlands, and Hong Kong - Ahwan Ahwan; Topo Santoso (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
The discontinuation of the investigation and prosecution of corruption crimes is one of the important substances of the amendment to Law No. 19 of 2019 concerning the Corruption Eradication Commission which then led to debates both among academicians and legal practitioners. The discourse focused on the essence and concerns of transactional practices in the process of law enforcement for corruption crimes in the future. By using the legal comparative method, this paper tries to compare the provisions regarding the discontinuation of the investigation and prosecution of corruption crimes in Indonesia, Hong Kong, and the Netherlands. The results of the study show that the provisions regarding the discontinuation of the investigation and prosecution of corruption crimes in the three countries have differences in their arrangements. Normatively, Indonesia and the Netherlands regulate this matter in several articles, while for Hong Kong, although they do not regulate it in an expressis verbis manner in the law, the provisions concerning the discontinuation of investigations and prosecutions of corruption crimes are known in their law enforcement practices as seen in the case handling scheme published by the Independent Commission Against Corruption (ICAC). However, the use of the mechanism for terminating the investigation and prosecution of corruption crimes can be seen as a balancing mechanism against the legal process. Regulations regarding the discontinuation of investigations in corruption crimes must be maintained as a control mechanism against the possibility of errors in law enforcement procedures or for other technical reasons.